2022
DOI: 10.1371/journal.pone.0277125
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of functional disability among older adults in Ghana: A multi-level analysis of the study on global ageing and adult health (SAGE) Wave II

Abstract: Background Functional disability is a common public health problem that affects the health and quality of life of older adults. This causes them to be highly dependent on other members of their family, receive home care, or to be institutionalized. Although functional disability has been widely studied in developed country settings, very limited studies have focused on age-related functional disability in sub-Saharan Africa, and in particular Ghana. The purpose of this study is to assess various factors associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Essa relação pode estar atrelada ao aumento das taxas de doenças e ao envelhecimento da população em escala global, visto que a vulnerabilidade nesse grupo se evidencia e há maior risco à saúde. Estudos apontam que as incapacidades funcionais que contribuem para o tipo de deficiência podem ampliar--se em outros aspectos, em conjunto com idade, gênero, doenças crônicas, residência rural e discriminação (11)(12)(13)(14) .…”
Section: Discussionunclassified
“…Essa relação pode estar atrelada ao aumento das taxas de doenças e ao envelhecimento da população em escala global, visto que a vulnerabilidade nesse grupo se evidencia e há maior risco à saúde. Estudos apontam que as incapacidades funcionais que contribuem para o tipo de deficiência podem ampliar--se em outros aspectos, em conjunto com idade, gênero, doenças crônicas, residência rural e discriminação (11)(12)(13)(14) .…”
Section: Discussionunclassified
“…Such research has not been explored in a sub-Saharan African context, as urban–rural distinctions in older adult health research are limited ( Kalu et al, 2021 ). Previous research using SAGE Ghana data has found that women report greater rates of ADL disability than men ( Amegbor et al, 2018 ), especially those with multiple chronic conditions ( Darkwah et al, 2022 ). Older Ghanaian women also report greater care needs than their men counterparts ( Awuviry-Newton et al, 2022a , 2022b ).…”
mentioning
confidence: 99%